2016
DOI: 10.1002/ccd.26628
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary practice patterns related to the risk of acute kidney injury in the catheterization laboratory: Results from a survey of Society of Cardiovascular Angiography and Intervention (SCAI) cardiologists

Abstract: The majority of cardiologists participating in this survey, reported practice patterns consistent with guideline and evidence-based recommendations. However, over 40% of responses to questions were inconsistent with these recommendations, suggesting continued opportunities for education and quality improvement concerning AKI prevention. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A recent landmark study of over 1.3 million PCIs by Amin et al demonstrated inconsistent and significant variation in contrast use among physicians and minimal reduction in CMV for patients at higher risk for AKI . In a recent physician survey carried out by SCAI, 40% of respondents reported estimating CMV without using a measurement technique and 40% of respondents reported not using CMV threshold limits for patients at risk of AKI …”
Section: Discussionmentioning
confidence: 99%
“…A recent landmark study of over 1.3 million PCIs by Amin et al demonstrated inconsistent and significant variation in contrast use among physicians and minimal reduction in CMV for patients at higher risk for AKI . In a recent physician survey carried out by SCAI, 40% of respondents reported estimating CMV without using a measurement technique and 40% of respondents reported not using CMV threshold limits for patients at risk of AKI …”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of diabetes, CKD, and peripheral arterial disease (PAD) continues to rise, an increasing number of patients will present for endovascular therapy and be exposed to the risk of CI‐AKI . The use of digital subtraction imaging with ICM remains the most common angiographic approach in patients with symptomatic PAD . Pharmacologic measures to reduce the incidence of CI‐AKI have been largely ineffective—with volume expansion and minimization of ICM as the most adopted techniques to prevent this complication.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, a low rate of hydration in patients of our study clearly suggests a weak understanding of both the disease and the therapy. A recent survey conducted by Prasad et al ., to evaluate contemporary practice patterns with regard to prevention of CIN in patients undergoing invasive angiography from the Society of Cardiovascular Angiography and Intervention (SCAI) member cardiologists, revealed that 96.8% of the patients believe that the acute kidney injury (AKI) risk was always important; however, there were only 64.8% cardiologists who inclined to adopt the use of standardized volume expansion protocols to prevent the occurrence of CIN23.…”
Section: Discussionmentioning
confidence: 99%